The effects of zinc oxide on the sinterability of hydroxyapatite - Ching T.Y.; Singh R.; Yong T.C.; Kar Y.B. (Institute of Electrical and Electronics Engineers Inc., 2023)
Ball milling; Doping (additives); Fracture toughness; Hardness; Hydroxyapatite; Powders; Sintering; Zinc; Phase formations; Relative density; Secondary phasis; Sinterability; Sintered samples; Sintering temperatures; Wet-chemical method; Zinc oxide (ZnO); Zinc oxide